Effect of depth of cut (DOC) and degree of serrations (DOS) on surface roughness of aluminum 6061 - Muhammad Sukroni; Heni Hendaryati; Iis Siti Aisyah (Journal of Energy, Mechanical, Material, and Manufacturing Engineering, 2022)
This study aims to determine the variation of the depth of cut (DOC) on the surface roughness and serration gram (DOS) in the 6061 aluminum turning process using medium speed. In this study the infeed depths used were 0.5 mm, 1 mm, 1.5 mm, and 2 mm by testing the surface roughness using a roughness tester, and testing the teeth gram (DOS) using the SEM (Scaning Electron Microscope) tester. The value of surface roughness (surface roughness) in relation to the depth of cut (DOC) in 6061 aluminum material using a conventional lathe has increased, while the value of the dentition gram (DOS) to the depth of cut (DOC) in the aluminum 6061 lathe process at a depth of 0.5 mm figure shows the percentage of DOS 31.8 percent then continues to decrease with increasing depth of ingestion on the lathe. Based on the research results, the increase in the surface roughness value was due to heat generation which resulted in damage to the chisel resulting in high surface roughness. In addition, variations in the depth of cut gave a negative effect by showing a decrease in the number of serrations in grams, which made it difficult to break and would result in eye damage. chisel